Contemporary concepts of specialist language education of law students in Poland and Germany towards the professionalization of education - Biedroń, Lena (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The European and Polish glottodidactics follow the changing reality of language education, which is influenced by the Council of Europe and the European Union’s promotion of plurilingualism and multilingualism. The analysis of the language education system at the law faculties in Poland and Germany aims at recognising the concept of language education of Polish and German law students, looking for innovative didactic and methodological solutions and for the way of implementing European standards by universities. Demonstration of curriculum similarities and differences in the field of teaching a foreign language against the background of legal regulations in the academic systems favours the development of new didactic solutions and encourages deeper reflection on the methods of professional education.